CORRECTION OF CAUDAL SEPTAL DEVIATIONS VIA CLOSED RHINOPLASTY APPROACH: Surgical Management of the Caudal Septal Deviations - Haq, Syed Nadeem Ul; Ahmed, Azeema; Ayub, Zeeshan (Pakistan Armed Forces Medical Journal, 2016)
Objective: To introduce the combined technique of nasal spine stitching and partial tongue-in-groove for the management of caudal septal deviation and to evaluate the surgical outcome and its efficacy. Study Design: Quasi-experimental study. Place and Duration of Study: Ear, nose and throat (ENT) Department Combined Military Hospital (CMH) Lahore from September 2013 to February 2015. Material and Methods: Ninety three patients with caudal deviation were included in the study. Caudal septal deviation was corrected employing both Modified Kriedel’s and Pastorek’s technique via endonasal approach. Nasal patency was determined using the alpha-version of "Nasal Obstruction Symptom Evaluation" (NOSE) Scale. Results: NOSE Scale scores were checked pre operatively and three weeks post surgery. Post operatively 88 (94.6%) patients had satisfactory nasal patency (NOSE Scale score fell by 15 points). Five (5.4%) patients who did not have satisfactory score had revision surgery. Conclusion: Combination of Pastoreks’s and Kriedel’s technique gives accurate correction of caudal dislocation.